2020
DOI: 10.3390/f11121303
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Variation of Transpiration and Its Modeling of a Larch Plantation in Semiarid Northwest China

Abstract: Quantifying the variation of forest transpiration (T) is important not only for understanding the water and energy budget of forest ecosystems but also for the prediction, evaluation, and management of hydrological effects as well as many other ecosystem services of forests under the changes of climate, vegetation, and anthropological impacts. The accurate prediction of T, a key component of water used by forests, requires mechanism-based models describing the T response to environmental and canopy conditions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…E c responded to REW as a saturated exponential function for C. korshinskii in this study (Figure 5c,d), which was in agreement with results reported for broadleaved and coniferous trees under different climates [41], a larch plantation in the semiarid Northwest China [42], a black locust plantation [43], and C. korshinskii [44] on the Loess Plateau. However, the REW threshold in this study is similar to or relatively higher than those in the studies reported above.…”
Section: Canopy Transpiration Of U Pumila and C Korshinskiisupporting
confidence: 91%
“…E c responded to REW as a saturated exponential function for C. korshinskii in this study (Figure 5c,d), which was in agreement with results reported for broadleaved and coniferous trees under different climates [41], a larch plantation in the semiarid Northwest China [42], a black locust plantation [43], and C. korshinskii [44] on the Loess Plateau. However, the REW threshold in this study is similar to or relatively higher than those in the studies reported above.…”
Section: Canopy Transpiration Of U Pumila and C Korshinskiisupporting
confidence: 91%
“…During the mounting process of the dendrometers, we removed the dead outer bark to place the sensor as close to the living tissue as possible, following a common practice for dendrometer measurements of trees (e.g. Grams et al., 2021; Oberhuber et al., 2020; Wang et al., 2020). This ensures that hygroscopic shrinkage and swelling of dead tissues from the outer bark does not influence the diameter measurements.…”
Section: Methodsmentioning
confidence: 99%
“…Here, comparative studies revealed a complex interplay of xylem as well as phloem growth and pressure-induced size changes, which simultaneously affect radial stem change and are thus captured by the dendrometers (TURCOTTE et al, 2011;KNÜSEL et al, 2021). Following a common practice for dendrometer measurements of trees (e.g., WANG et al, 2020), the dead outer bark was therefore removed to place the sensor as close to the living tissue as possible and to eliminate the effects of such processes.…”
Section: Dendrometer Measurementsmentioning
confidence: 99%
“…We mounted our dendrometers on one major aboveground stem of a randomly chosen specimen per site, horizontally to the ground surface and as close to the assumed root collar as possible. During this process, we removed the dead outer bark (periderm) to place the sensor as close to the living tissue as possible, following a common practice for dendrometer measurements of trees Wang et al, 2020;. This ensures that hygroscopic shrinkage and swelling of dead tissues from the outer bark do not influence the diameter measurements.…”
Section: Dendrometric Data and Monitoring Setupmentioning
confidence: 99%
See 1 more Smart Citation